Zinc Absorption From Agronomically Biofortified Wheat Is Similar to Post-Harvest Fortified Wheat and Is a Substantial Source of Bioavailable Zinc in Humans. Issue 5 (20th April 2019) - Signorell, Coralie; Zimmermann, Michael B; Cakmak, Ismail; Wegmüller, Rita; Zeder, Christophe; Hurrell, Richard; Aciksoz, Seher B; Boy, Erick; Tay, Fabian; Frossard, Emmanuel; Moretti, Diego
ABSTRACT: Background: Limited data exist on human zinc absorption from wheat biofortified via foliar (FBW) or root (hydroponically fortified wheat, HBW) zinc application. Stable isotope labels added at point of consumption (extrinsic labeling) might not reflect absorption from native zinc obtained by intrinsic labeling. Objectives: We measured fractional and total zinc absorption (FAZ, TAZ) in FBW and HBW wheat, compared with control wheat (CW) and fortified wheat (FW). The effect of labeling method was assessed in HBW (study 1), and the effect of milling extraction rate (EXR, 80% and 100%) in FBW (studies 2 and 3). Methods: Generally healthy adults ( n = 71, age: 18–45 y, body mass index: 18.5–25 kg/m 2 ) were allocated to 1 of the studies, in which they served as their own controls. In study 1, men and women consumed wheat porridges colabeled intrinsically and extrinsically with 67 Zn and 70 Zn. In studies 2 and 3, women consumed wheat flatbreads (chapatis) labeled extrinsically. Zinc absorption was measured with the oral to intravenous tracer ratio method with a 4-wk wash-out period between meals. Data were analyzed with linear mixed models. Results: In study 1 there were no differences in zinc absorption from extrinsic versus intrinsic labels in either FW or HBW. Similarly, FAZ and TAZ from FW and HBW did not differ. TAZ was 70–76% higher in FW and HBW compared with CW ( P < 0.01). In studies 2 and 3, TAZ from FW and FBW did not differ but was 20–48% higher compared with CW ( P < 0.001). Extraction rate had no effect on TAZ. Conclusions: Colabeling demonstrates that extrinsic zinc isotopic labels can be used to accurately quantify zinc absorption from wheat in humans. Biofortification through foliar zinc application, root zinc application, or fortification provides higher TAZ compared with unfortified wheat. In biofortified wheat, extraction rate (100–80%) has a limited impact on total zinc absorption. These studies were registered on clinicaltrials.gov (NCT01775319).